Adeno-associated virus: a key to the human genome? - Henckaerts, Els (2010)
Adeno-associated viruses (AAV) are widely spread throughout the human population, yet no pathology has been associated with infection. This fact, together with the availability of simple molecular techniques to alter the packaged viral genome, has made AAV a serious contender in the search for an ideal gene therapy delivery vehicle. However, our understanding of the intriguing features of this virus is far from exhausted and it is likely that the mechanisms underlying the viral lifestyle will reveal possible novel strategies that can be employed in future clinical approaches. One such aspect is the unique approach AAV has evolved in order to establish latency. In the absence of a cellular milieu that will support productive viral replication, wild-type AAV can integrate its genome site specifically into a locus on human chromosome 19 (termed AAVS1), where it resides without apparent effects on the host cell until cellular conditions are changed by outside influences, such as adenovirus super-infection, which will lead to the rescue of the viral genome and productive replication. This article will introduce the biology of AAV, the unique viral strategy of targeted genome integration and address relevant questions within the context of attempts to establish therapeutic approaches that will utilize targeted gene addition to the human genome.